Laparoscopic versus open surgery for left flexure colon cancer: A propensity score matched analysis from an international cohort. (9th November 2021) - Pedrazzani, Corrado; Turri, Giulia; Park, Soo Yeun; Hida, Koya; Fukui, Yudai; Crippa, Jacopo; Ferrari, Giovanni; Origi, Matteo; Spolverato, Gaya; Zuin, Matteo; Bae, Sung Uk; Baek, Seong Kyu; et al.
Abstract: Aim: Surgical treatment of splenic flexure cancer (SFC) still presents some debated issues, including the role of laparoscopic surgery. The literature is based on small single‐centre series, while randomized controlled studies comparing open and laparoscopic treatment for colon cancer exclude SFC. This study aimed to determine the role of laparoscopic surgery in the treatment of SFC, comparing short‐ and long‐term outcomes with open surgery. Method: This was an international multicentre retrospective cohort study that analysed patients from 10 tertiary referral centres. From a cohort of 641 cases, 484 patients with Stage I–III SFC submitted to elective surgery with curative intent were selected. After 1:1 propensity score matching, 130 patients in the laparoscopic group (LapGroup) were compared with 130 patients in the open surgery group (OpenGroup). Results: After propensity score matching, the two groups were comparable for demographic and clinical parameters. OpenGroup presented a higher incidence of overall ( P  = 0.02) and surgery‐related complications ( P  = 0.05) but a similar rate of severe complications ( P  = 0.75). Length of stay was notably shorter in the LapGroup ( P  = 0.001). Overall ( P  = 0.793) as well as cancer‐specific survival ( P  = 0.63) did not differ between the two groups. Conclusions: Elective laparoscopic surgery for Stage I–III SFC is feasible and associated with improved short‐term postoperative outcomes compared to open surgery. Moreover, laparoscopic surgery appears to provide excellent long‐term cancer outcomes.